1996
DOI: 10.1136/jmg.33.5.399
|View full text |Cite
|
Sign up to set email alerts
|

Small extra ring chromosome derived from chromosome 10p: clinical report and characterisation by FISH.

Abstract: We present a case with a small extra ring chromosome which was found in 66% of lymphocytes on routine cytogenetic examination. FISH analyses, using centromere specific and single copy probes, showed that the extra ring chromosome was derived from the most proximal part of lOp, close to the centromere. The patient has a unilateral cleft lip and palate, mild dysmorphic features, and mild mental retardation. Only a limited number of extra ring chromosomes have been characterised so far. To our knowledge, this is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0

Year Published

1998
1998
2004
2004

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 24 publications
1
32
0
Order By: Relevance
“…For SRCs Blennow and Tillberg (1996) estimated the risk of an abnormal phenotype of about 60 %. Important factors, determining whether or not an SRC will give rise to a clinical phenotype, are the euchromatic material involved and the degree of mosaicism.…”
Section: Discussionmentioning
confidence: 99%
“…For SRCs Blennow and Tillberg (1996) estimated the risk of an abnormal phenotype of about 60 %. Important factors, determining whether or not an SRC will give rise to a clinical phenotype, are the euchromatic material involved and the degree of mosaicism.…”
Section: Discussionmentioning
confidence: 99%
“…The degree of mosaicism varied from 35 to 100 %. Regarding the size and the content of euchromatic material of the ring from proximal 10p and 10q, only two of the SMCs reviewed in the literature are cytogenetically comparable to our case (Blennow and Tillberg, 1996;Schlegel et al, 2002), with only the first of them being described clinically after birth showing a small ring-shaped SMC including the proximal short arm and centromeric sequences of chromosome 10 only (Blennow and Tillberg, 1996;Anderlid et al, 2001). Two of the other cases involve a marker chromosome consisting of the whole short arm of chromosome 10 (Snyder et al, 1984;Chen et al, 2001), while the case reported by Levy et al (2000), had a partial tetrasomy of more distal bands of 10p (10pter → p14F15) with neocentromere formation.…”
Section: Discussionmentioning
confidence: 85%
“…To the best of our knowledge, only five supernumerary marker chromosomes derived from chromosome 10 have been reported up today (Snyder et al, 1984;Blennow and Tillberg, 1996;Levy et al, 2000;Chen et al, 2001;Schlegel et al, 2002; see Table 1). The SMCs were de novo in all cases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations